Entrepreneurship in agricultural education in the light of three epistemological approaches: A systematic review - Villamarín - Monroy, Jeffer Julián; Montalvo - Rodríguez, Juan Carlos (Universidad Francisco de Paula Santander, 2023)
One of the ways to overcome the economic and productive needs of different rural areas is through entrepreneurship. For this reason, studying from the paradigms such as phenomenology, constructivism, and empiricism, manages to cover the different questions and gaps that arise in the incidences for the development of young people in agricultural entrepreneurship activities.  However, entrepreneurship provides solutions to economic and social problems in each region. In this way it also manages to stimulate in the young people of agricultural school’s notions of entrepreneurship, and generates contributions in the transformation of environments, increasing the economic dynamics adapted in the regions, which finally contribute to the development of young people, and the acquisition of entrepreneurial skills. A systematic review of articles published in journals indexed in English and Spanish of research contributions on training issues in agricultural entrepreneurship is carried out, the experiences that are given according to the conditions and characteristics of each of the different studies carried out, and their adaptability in rural environments based on the paradigms that frame these conditions in each of the regions at a global level.